Algorithm Theory -- SWAT 2012 13th Scandinavian Symposium and Workshops, Helsinki, Finland, July 4-6, 2012, Proceedings - Fomin, Fedor V.; Kaski, Petteri; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 13th International Scandinavian Symposium and Workshops on Algorithm Theory, SWAT 2012, held in Helsinki, Finland, in July 2012, co-located with the 23rd Annual Symposium on Combinatorial Pattern Matching, CPM 2012. The 34 papers were carefully reviewed and selected from a total of 127 submissions. The papers present original research and cover a wide range of topics in the field of design and analysis of algorithms and data structures.
Keywords: Algorithms; Computer science—Mathematics.; Data structures (Computer science).; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Data Structures; Algorithms